Medicinal plants with antimicrobial, larvicidal, and repellent properties: An ethnopharmacological survey from the Democratic Republic of the Congo - Kyana, Joseph; Luzala, Miryam M.; Muanga, Claude-Josué K.; Zola, Eunice N.; Wendji, Sébastien N.; Vuangi, Benny M.; Biniandgie, Patience M.; Ketty, Christelle T.; Tshimanga, Guillaume M.; Ndonga, Aimé L.; Kasongo, Jonathan B.; Eyobi, Vinel M.; et al. (Orapuh Journal, 2024)
IntroductionInfectious diseases (IDs) constitute a real public health problem in the Democratic Republic of the Congo (DRC). PurposeThis survey aimed to gather more information about the plants used in the DRC for anti-infective, larvicidal, or repellent treatments. MethodsThe study spanned 4 months (from April 1 to July 31, 2022) within 11 provinces in the DRC and was conducted among 20 traditional healers (TH), 105 vegetable growers (VG), and 953 other plant users (OU) of traditional plants scattered across the country. The survey consisted of a simple interview with an inventory of the plants used. Results The results showed that the average age of the respondents was between 39 and 43 years old. The VG were mainly illiterate. As for TH and OU, literacy rates up to the primary level were 60% and 78%, respectively. The knowledge of the use of plants by the various actors of traditional medicine in this survey emanates from the cultural heritage. For this study, 132 plant species (104 identified and 28 unidentified based on their botanical name or family) were reported. 33 antimicrobial species and 7 larvicidal species belonging to 22 botanical families have been reported among TH, while 1 and 75 antimicrobial species, 6 and 16 larvicidal species, and 13 and 30 repellent species were respectively identified among VG and OU. This study identified Morinda morindoides, Cymbopogon citratus, and Boswellia sacra as the plant species most used by the individuals surveyed for anti-infective, larvicidal, and repellent treatments, respectively, by their citation frequencies, which were the highest. Additionally, the leaves represented the plant parts most used by the respondents. ConclusionThis ethnobotanical analysis revealed that most herbal antimicrobial recipes are used to treat malaria. This study confirms the richness of the Congolese flora concerning anti-infective, larvicidal, and repellent treatments.